Mathematics Teachers' Understanding in Developing Learning Indicators in Preparing Lesson Plans: Pemahaman Guru Matematika dalam Mengembangkan Indikator Pembelajaran dalam Menyusun Rencana Pelaksanaan Pembelajaran (RPP) - Nopriana, Tri; Dian Nopitasari; Dahlan, Jarnawi Afgani (Pedagogia : Jurnal Pendidikan, 2021)
Research on teachers' ability to prepare lesson plans has not shown good results, whereas there have been many studies on efforts to improve teachers in preparing lesson plans. Still, no research explicitly describes the ability of teachers to develop indicators. This research aims to describe the understanding of mathematics teachers in creating learning indicators. This research is quantitative research with a survey method. The sur- vey was conducted on 51 Mathematics Teachers in Cirebon City. The research instrument used was in the form of a questionnaire regarding the indicators of developing learning indicators. The results showed that (1) most teachers still did not understand the steps of developing learning indicators (2) teachers still had difficulty determining operational verbs (KKO) of knowledge, conducting processes, implementation, and evaluation, (3) there were still teachers who thought the affective and psychomotor aspects could not be assessed in mathematics, (4) most teachers have developed at least three indicators in a basic competency, while almost half of the sample assumes the characteristics of students and schools do not affect developing learning indicators.